Validation of the Early Childhood Affective Ability and Behavior Questionnaire on Self-Protection from Suspicious Touches - Esa Risi Suazini, Esa Risi Suazini; Rosita Alvia, Rosita Alvia (Jurnal Medika Cendikia, 2025)
Victims of sexual violence are predominantly children. This is due to a lack of understanding of the boundaries of "appropriate touch" on the body. An age- and culturally-appropriate measurement tool is needed to support their self-protection education efforts. This tool will assess children's readiness to identify and respond to suspicious touch. The purpose of this study was to design and test a questionnaire that serves as a measure of knowledge, affective and psychomotor expressions of children aged 5 to 8 years. This questionnaire is also useful as a medium for educating children to avoid sexual violence. This study used an exploratory mixed-method design. Content validity was assessed by three experts, face validity was assessed through observation of 13 children. Item-total correlation analysis and Cronbach's Alpha were used to assess reliability and empirical validity on 62 students from three schools. Results showed that all 28 items were valid by experts (I-CVI and S-CVI/Ave=1.00), and all had r values greater than 0.246. Cronbach's Alpha values were highly reliable for the self-protection section (0.983) and the expression of affection section (0.974). Therefore, this questionnaire can be used by parents, health workers, and teachers, to measure and educate children to prevent sexual violence.